2009
DOI: 10.2174/1874375700903010106
|View full text |Cite
|
Sign up to set email alerts
|

Severely Atrophic Muscle Fibers with Nuclear Clumps Survive many Years in Permanently Denervated Human Muscle

Abstract: After complete lumbar-ischiatic spinal cord injury (SCI) the lower motor neuron (LMN) denervated human muscle fibers lose completely the myofibrillar apparatus and the coil distribution of myonuclei that are relocated in groups (nuclear clumps) in the center of these "severely atrophic" muscle fibers. In our cohort of patients, the "severely atrophic" myofibers are frequent in muscle biopsies harvested three to six years after SCI. Up to two years of LMN denervation the muscle fibers with nuclear clumps are 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…36 Finally, muscles enter severe atrophy, wherein myofibers undergo the internalization of subsarcolemmal myonuclei, resulting in the regrouping of tens of myonuclei within the center of myofibers and the complete disappearance of long segments of the contractile apparatus. 13 Eventually, muscle fibers all but completely disappear, while fibrous and adipose tissue accumulates.…”
Section: Effects Of Long-lasting Complete Denervation Of Human Musclesmentioning
confidence: 99%
See 3 more Smart Citations
“…36 Finally, muscles enter severe atrophy, wherein myofibers undergo the internalization of subsarcolemmal myonuclei, resulting in the regrouping of tens of myonuclei within the center of myofibers and the complete disappearance of long segments of the contractile apparatus. 13 Eventually, muscle fibers all but completely disappear, while fibrous and adipose tissue accumulates.…”
Section: Effects Of Long-lasting Complete Denervation Of Human Musclesmentioning
confidence: 99%
“…37 Additional investigations in human patients showed that irrecoverable muscle tissue degeneration can be delayed up to three years, and indeed light microscopy analysis showed that myofibers retain at least 30% of their initial size over this duration, confirming at least a two-year window for possible FES intervention. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, electron microscopy investigations on patients biopsies indicated that the decay of excitationcontraction contractile apparatus, i.e., of t-tubules and triads, starts within one year of denervation, suggesting that for the best results the h-b FES treatment must start as early as possible. 14,15,17 …”
Section: Effects Of Long-lasting Complete Denervation Of Human Musclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The bioenergetic function of mitochondria in a tissue is evaluated by OXPHOS analysis and depends on mitochondrial structure and function [1][2][3][4]. Mitochondrial structure or mt-density is determined by measurement of mtmarkers normalized for tissue mass or volume.…”
mentioning
confidence: 99%